GE_GERICHTE P/633/2012 vom 9. Januar 2019 - GE Cour de justice (2019)
CONTRAVENTION DE POLICE DE DROIT CANTONAL ; FRAIS DE LA PROCÉDURE ; DÉPENS | LGD.43; LCI.137; CPP.426.al1; CPP.428.al1; CPP.429.al1